THE ROLE OF VOCABULARY IN EFFECTIVE ENGLISH COMMUNICATION (Web of Teachers: Inderscience Research, 2025)
Vocabulary acquisition is a fundamental aspect of language learning, significantly impacting communication skills. This study explores effective methods for vocabulary retention and application, emphasizing the importance of student-centered learning, interactive activities, and digital tools. The research highlights the role of storytelling, role-playing, and speaking exercises in reinforcing vocabulary knowledge. Additionally, it examines the impact of modern technology, such as gamified learning, adaptive systems, and multimedia resources, in enhancing long-term vocabulary retention. The findings suggest that a combination of interactive learning strategies and digital support leads to more effective vocabulary acquisition and application in real-world contexts.